Magnetic direct-write skyrmion nanolithography - Ognev, Alexey V; Kolesnikov, A. G.; Kim, Yong Jin; Cha, In Ho; Sadovnikov, Alexandr V.; Nikitov, S. A.; Soldatov, Ivan; Talapatra, A.; Mohanty, Jyoti; Mruczkiewicz, Michal; Ge, Y.; Kerber, Nico; et al. (ACS nano, 2020)
Magnetic skyrmions are stable spin textures with quasi-particle behavior and attract significant interest in fundamental and applied physics. The metastability of magnetic skyrmions at zero magnetic field is particularly important to enable, for instance, a skyrmion racetrack memory. Here, the results of the nucleation of stable skyrmions and formation of ordered skyrmion lattices by magnetic force microscopy in (Pt/CoFeSiB/W)n multilayers, exploiting the additive effect of the interfacial Dzyaloshinskii-Moriya interaction, are presented. The appropriate conditions under which skyrmion lattices are confined with a dense two-dimensional liquid phase are identified. A crucial parameter to control the skyrmion lattice characteristics and the number of scans resulting in the complete formation of a skyrmion lattice is the distance between two adjacent scanning lines of a magnetic force microscopy probe. The creation of skyrmion patterns with complex geometry is demonstrated, and the physical mechanism of direct magnetic writing of skyrmions is comprehended by micromagnetic simulations. This study shows a potential of a direct-write (maskless) skyrmion (topological) nanolithography with sub-100 nm resolution, where each skyrmion acts as a pixel in the final topological image.
CRIS-Team Scopus Importer:2023-03-27
Keywords: Interfacial Dzyaloshinskii-Moriya interaction; Magnetic force microscopy; Perpendicular magnetic anisotropy; Skyrmion; Topological nanolithography